2022
DOI: 10.32604/csse.2022.022122
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient On-Demand Virtual Machine Migration in Cloud Using Common Deployment Model

Abstract: Cloud Computing provides various services to the customer in a flexible and reliable manner. Virtual Machines (VM) are created from physical resources of the data center for handling huge number of requests as a task. These tasks are executed in the VM at the data center which needs excess hosts for satisfying the customer request. The VM migration solves this problem by migrating the VM from one host to another host and makes the resources available at any time. This process is carried out based on various al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…An organization may more effectively build long-term goals to improve its operations and concurrently respond with intelligence to events that occur as a result of putting real-time business intelligence (BI) into action inside the organization. Have examined how business intelligence affects small and medium sized businesses along with the benefits and problems associated with it in [10]. Utilizing information effectively is one of the most important success criteria for businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An organization may more effectively build long-term goals to improve its operations and concurrently respond with intelligence to events that occur as a result of putting real-time business intelligence (BI) into action inside the organization. Have examined how business intelligence affects small and medium sized businesses along with the benefits and problems associated with it in [10]. Utilizing information effectively is one of the most important success criteria for businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e study was carried out using WEKA ML equipment and an actual database from the American corporation Orange. Saravana Kumar et al [12] suggested a CCP technique that employs soft voting and SACtacking models via an ensemble learning method. Machine learning methods Xgboost, LR, DT and NB are utilised to build a two-stage stacking approach, with the three outputs of the succeeding level used for soft voting.…”
Section: Existing Ccp Models For Telecommunication Sectormentioning
confidence: 99%
“…Through the course of our research, we were able to distinguish and categorize the most prevalent types of virtualization, as depicted in Table 5 and illustrated in Figure 7. These types broadly encompass virtualization of servers, networks, storage, data, desktops, and applications (Li et al, 2022;Liu., 2021;Nazarov et al, 2020;Park et al, 2021;Pons, et al, 2022;Qazi, 2020;Radchenko et al, 2019;Rosioru et al, 2022;Saravanakumar et al, 2022). The diversity in types of virtualization underscores the broad applicability and immense potential of this technology in transforming various aspects of computing and information technology.…”
Section: Current Types Of Virtualizationmentioning
confidence: 99%